Ecocriticism : the essential reader - Hiltner, Ken (London ; New York : Routledge, 2015)
"Ecocriticism: The Essential Reader charts the growth of this important field. The first-wave ecocriticism section focuses on key readings from the 1960s to the 1990s. The second-wave ecocriticism section goes on to consider a range of exciting contemporary trends, including environmental justice, aesthetics and philosophy, and globalization.Readings include the work of:Raymond WilliamsJonathan BateTimothy MortonUrsula HeiseLawrence BuellKate SoperCary Wolfeand Kate Rigby.Containing seminal, representative, and contemporary work in the field, this volume and the editorial commentary is designed for use on both undergraduate and postgraduate ecocritical literature courses"--
"Ecocriticism: The Essential Reader Ecocriticism: The Essential Reader charts the growth of this important field. The first-wave Ecocriticism section focuses on key readings from the 1960s to the 1990s. The second-wave Ecocriticism section goes on to consider a range of exciting contemporary trends, including environmental justice, aesthetics and philosophy, and globalization. Readings include the work of: - Raymond Williams - Jonathan Bate - Timothy Morton - Ursula Heise - Lawrence Buell - Kate Soper - Cary Wolfe - Kate Rigby. Containing seminal, representative, and contemporary work in the field, this volume and the editorial commentary is designed for use on both undergraduate and postgraduate ecocritical literature courses"--
Part 1: First-Wave Ecocriticism 1. Shakespeare's American Fable, Leo Marx 2. Nature As Female, Carolyn Merchant 3. Country and City, Raymond Williams 4. The Historical Roots of Our Ecologic Crisis, Lynn White Jr. 5. The Deep Ecological Movement: Some Philosophical Aspects, Arne Naess 6. Introduction: Ecology and Man-A Viewpoint, Paul Shepard 7. The Etiquette of Freedom, Gary Snyder 8. The Economy of Nature, Jonathan Bate 9. Representing the Environment, Lawrence Buell 10. The Trouble with Wilderness; or, Getting Back to the Wrong Nature, William Cronon 11. Introduction: Literary Studies in an Age of Environmental Crisis, Cheryll Glotfelty Part 2: Second-Wave Ecocriticism 12. The Environmental Justice Reader: Politics, Poetics & Pedagogy, Joni Adamson, Mei Mei E.vans, and Rachel Stein 13. Introduction: Emerging Models of Materiality in Feminist Theory, Stacy Alaimo 14. Race, Class, and the Politics of Place, Robert D. Bullard 15. Queer Ecologies: Sex, Nature, Politics, Desire, Catriona Mortimer-Sandilands 16. The Hitchhiker's Guide to Ecocriticism, Ursula K. Heise 17. Introduction, Graham Huggan 18. Environmentalism and Postcolonialism, Rob Nixon 19. Natural Universal and the Global Scale, Anna Lowenhaupt Tsing 20. Conclusion: What Is to Be Done? Political Ecology!, Bruno Latour 21. Imagining Ecology Without Nature, Timothy Morton 22. The Truth of Ecology: Nature, Culture and Literature in America, Dana Phillips 23. What is Nature? Culture, Politics and the non-Human, Kate Soper 24. Ecopolitics/ Ecocriticism, Gabriel Egan 25. Reading The Otherworld Environmentally, Alfred Siewers 26. Introduction: Troping the Tropics and Aestheticizing Labor, Beth Tobin 27. Ecology, Epistemology, and Empiricism, Robert N. Watson 28. The Climate of History: Four Theses, Dipesh Chakrabarty 29. The Carrier Bag Theory of Fiction, Ursula LeGuin 30. Writing After Nature, Kate Rigby
Includes bibliographical references and index.
ENG
Trim Education
Keywords: Ecocriticism; Ecology in literature; Environmental protection in literature; LITERARY CRITICISM / General; English literature